Effect of Technology and Market Dynamism on the Business Performances of SMEs by Supporting Services. (March 2019) - Park, Hun; Yoo, Jae-Young; Moon, Seong-Hee; Yoo, Hyoung-Sun; Lee, Ho-Shin; Kwon, Tae-Hoon; Hahn, Hyuk
Research objective of our study is to find the effect of technology and market dynamism on the business performances by small- and medium-sized enterprises (SME) supporting services. Technology and market dynamism have been introduced as moderating variables, utilisation degree of information provided by SME supporting services was selected as an independent variable and contribution degree to SME business performances such as revenue, export, employment and so on were selected as dependent variables. Structural equation modeling was established to analyse moderating and mediating effects on SME business performances by SME supporting services using Smart PLS programme. The SME supporting services had a direct effect on SME business performances and also indirectly influenced SME business performances via contribution degree to decision-making of SME executives. Technology and market dynamism significantly moderated the effect of decision-making of SME executives on SME business performances. It could be seen that technology and market dynamism had a mediated-moderating effect on SME business performances.